论郁达夫创作手法的转变 = Discussing the change in Yu Da Fu’s style of writing - 李姝静 Lee, Shu Jing (2011)
郁达夫（以下简称“郁”）前创作期的特色，是在一个正试图脱离封建保守思想的社会里大胆地进行自我暴露，把自己的内心世界赤裸裸地呈现在读者面前。前期作品表现的，是他那种感伤地 “自叙”身边事与自己身为“零余者”的生活。然而，创作风格是随着时代环境走，有变化是必然的。留学回国后，因环境改变，他开始关注中国社会情况与人民生活。留在中国定居后，他更是受到环境与人群影响，小说便不仅只写社会，也写人群的心理。后期作品创作风格，便是偏离浪漫主义，偏向现实主义。实际上，他创作手法上的转变，一直是具有争议性的话题。有人支持1923年开始分前后期，又有人支持1927年才是后期的开始。但不容忽视的，人生本来就有许多的过渡期，不一定一个过渡期就会形成一个转折点。郁的过渡期或许并不足以构成一个完整的风格改变，而只是他开始有所领悟的一段时期。本篇将试以1919年至1926年作为郁前期的创作生涯；以1927年至1935年作为后期创作生涯；探讨他创作上的风格在这前、后两期有什么样的不同，有什么样的影响因素与他思想情感上的变化是如何影响了他创作上的内容与人物塑造，从而判定1926-1927作为分期是否准确。本篇也将探讨在摆脱了限制后，郁如何在改变的过程里保留自己一贯的特色。The early stage of Yu Dafu’s writing career displayed a unique characteristic of his writing style, which was to base his writing materials on his life experiences and innermost emotions. He came from a conservative society which was still trying to break free from the feudalism system. This however did not hinder him from boldly exposing his “naked” self to readers through his works. During the early stage, his works presented a sentimental atmosphere, where he seemed to be writing monologues about only his life and his feelings. The works also portrayed his role as an outcast in his surroundings. The later stage of his writing career however showed a change in his style of writing due to a change in environment and times, which eventually affected his perception of life and society. That was when he began to express his concern for social issues and the psychological aspects of people who were constantly living in poverty.